Application perspectives of localization microscopy in virology - Cremer, Christoph; Gunkel, Manuel; Müller, Patrick; Hausmann, Michael (Histochemistry and cell biology, 2014)
Localization microscopy approaches allowing an optical resolution down to the single-molecule level in fluorescence-labeled biostructures have already found a variety of applications in cell biology, as well as in virology. Here, we focus on some perspectives of a special localization microscopy embodiment, spectral precision distance/position determination microscopy (SPDM). SPDM permits the use of conventional fluorophores or fluorescent proteins together with standard sample preparation conditions employing an aqueous buffered milieu and typically monochromatic excitation. This allowed superresolution imaging and studies on the aggregation state of modified tobacco mosaic virus particles on the nanoscale with a single-molecule localization accuracy of better than 8 nm, using standard fluorescent dyes in the visible spectrum. To gain a better understanding of cell entry mechanisms during influenza A virus infection, SPDM was used in conjunction with algorithms for distance and cluster analyses to study changes in the distribution of virus particles themselves or in the distribution of infection-related proteins, the hepatocyte growth factor receptors, in the cell membrane on the single-molecule level. Not requiring TIRF (total internal reflection) illumination, SPDM was also applied to study the molecular arrangement of gp36.5/m164 glycoprotein (essentially associated with murine cytomegalovirus infection) in the endoplasmic reticulum and the nuclear membrane inside cells with single-molecule resolution. On the basis of the experimental evidence so far obtained, we finally discuss additional application perspectives of localization microscopy approaches for the fast detection and identification of viruses by multi-color SPDM and combinatorial oligonucleotide fluorescence in situ hybridization, as well as SPDM techniques for optimization of virus-based nanotools and biodetection devices.
Gesehen am 23.09.2020